Online trip advisory system - Yip, Sook Chan (2010)
Travelling had been proven to have a lot of benefits. People get to relax their bodies and souls, increases knowledge, widen perspective, and enrich memory of travelling together with family and friends. Tourism in another hand, has also contributed significantly to the economy of Malaysia The government has not only formed ministry to govern tourism, arts and culture in Malaysia, incentives and facilities are also offered to any parties or authorities that wish to develop or improve the tourism industry in Malaysia. Tourists had always had problems in deciding where should they go for holidays and bow much would they spend during the holiday; Thus, Online Trip Advisory System (OTAS) is a solution to the problems. OTAS is a web-based system that uses questionnaire method to determine the preferences of the users. Based on the preferences captured from the questionnaire, OTAS implements rule-based technique to recommend to user the places to go for travel purposes. There is another questionnaire that is used to estimate the trip expenses for users. The answers of the questionnaire are the criteria of the trip planned by user. By implementing rule-based technique, OTAS is able to estimate the trip expenses for the users.